Educational reconstruction in Central Mindanao a model for promoting the psychosocial recovery and well-being of war-affected children and youth. - Muncy, Steven (2003)
The general objective of this action research initiative was to develop - in a collaborative manner - the Educational Reconstruction Model for promoting the psychosocial recovery and well-being of war-affected children and youth in Central Mindanao. The people in Inug-ug, Pagalungan, Maguindanao and service providers of Community and Family Services International (CFSI) were the focus of the initiative. The expected impact and outcomes included specific policy decisions on the part of the community to reduce child and youth exposure to violence and in an intervention paradigm shift on the part of the service provider. The methods were primarily, but not exclusively, qualitative in nature. Quantitative efforts involved 1,053 respondents and multivariate regression analysis. The role of the researcher was a combination of social planner, facilitator of learning, and catalyst for change. A dramatic deterioration in the security conditions in Central Mindanao and the temporary displacement of the entire population of Inug-ug were signficant constraints to the full implementation of the research plan. Much was learned about the community's exposure to violence and practices. Exposure was high. Gender, age, and education were associated with certain responses. Efforts to maintain or quickly restore family unity were recognized. Collaborative effort on the part of the community, sometimes at high cost, was underscored. Much was also learned about the knowledge and attitudes of service providers. Definitions of psychosocial varied considerably. A bias for recovery efforts - rather plan promotion of well-being - confirmed the need for a paradigm shift. Collaborative effort led to significant policy decisions, including the declaration of the Inug-ug Elementary School as a "Zone of Peace". This development and other efforts should, theoretically, help prevent exposure to violence and promote the psychosocial well-being of children and youth. However, the capacity of the community to actually carry out policy decisions was questionable owing to the power and behavior of the Armed Forces of the Philippines (AFP) and the Moro Islamic Liberation Front (MILF). There is a reason to believe the Educational Reconstruction Model could prove helpful in promoting the psychosocial well-being of war-affected children and youth. However, greater input from the community and service providers is required. Testing in a more stable environment and in different, but somewhat similar, situations is highly recommended.